An inquiry on general equilibrium effects of MERCOSUR: an intertemporal world model - Diao, Xinshen; Somwaru, Agapi (Elsevier, 2000)
A multiregion dynamic computable general equilibrium model is constructed to analyze effects of the Southern Common Market (MERCOSUR) on the member countries as well as third-party nonmember countries. The model is based on intertemporal optimization behaviors of consumers and firms with eight endogenously specified regions. By taking into account dynamic general equilibrium adjustments, we observe significant shifts of trade diversion away from the nonmember trading partners to the member countries. We also find that, following the MERCOSUR's common external tariffication, growth of intraregional trade would likely be accompanied by increases in trade between MERCOSUR and other countries. In this case, not only MERCOSUR member countries gain more, but also the nonmember countries are better off in terms of their production, consumption, and consumer welfare." -- Authors' Abstract